3.0 GA OLONDO GREENSTONE BELT IN THE ALDAN SHIELD, E. SIBERIA - Puchtel I.S. (My University, 2004)
The Olondo greenstone belt is a unique structure lying in the Aldan Shield. The Aldan Shield is the largest basement salient in the Siberian craton. The Subgan granite-greenstone complex includes sedimentary, volcaniclastic and volcanic rocks of greenstone belts, which have undergone polyphase greenschist to amphibolites facies deformation and metamorphism. The Olondo synform is characterized by a rather symmetrical distribution of various volcanic rock types with respect to the axis of the V-shaped structure. Contacts between the supracrustal rocks and the surrounding tonalitic–trondhjemitic gneisses are tectonic. Numerous tonalite plutons intruded along the contacts between the TTG and the greenstone sequences. Mafic and ultramafic plutonic rocks constitute a substantial part of the Olondo complex. Ultramafic plutonic rocks are mostly represented by large dunite–peridotite bodies that have clear tectonic relationships with the country rocks. The presence of high-Mg lavas such as the Western komatiites and Eastern komatiitic basalts with boninite-like geochemical and isotopic signatures indicates greater degrees of mantle melting above a subduction zone induced by fluids from a downgoing slab having lowered the melting point.